VEGETATION COMPOSITION OF WEED SPECIES IN SUGARCANE (SACCHARUM OFFICINARUM) CROPS IN THE LOWLAND AREAS OF SIDOARJO AND THE HIGHLAND AREAS OF MOJOKERTO - Tarigan, Puji Lestari; Septyaputri, Kurnia Adisya; Fifianah, Hanip Nur; Putri, Novi Dwi Mahendra; Firmansyah, Hanif; Novita, Maya (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Weed Species Diversity in Lowland and Upland Sugarcane (Saccharum officinarum) Fields: Sugarcane (Saccharum officinarum L.) cultivation began intensively on the northern coast of Java Island from the 1830s to the 1870s. Because of the presence of weeds that can interfere with the growth of major crops such as sugarcane, it is important to identify and manage these weeds to maintain productivity levels. Weed competition for nutrients, water, and light can significantly reduce crop yields. Agricultural land in Indonesia is divided into two main categories: lowland and upland, each with different environmental characteristics and weed species. Identification and utilization of weeds in lowland and upland sugarcane fields are essential for effective land management and increasing agricultural sustainability. Practices such as integrated weed management, which involves cultural, mechanical, biological, and chemical control strategies, play an important role in controlling weeds and ensuring maximum crop productivity. Factors that influence weed diversity in these areas are complex, including environmental factors such as temperature, humidity, and soil type, as well as agricultural practices such as pesticide use, crop rotation, and soil management. Collaborative efforts in implementing various weed control methods are essential in addressing weed challenges and optimizing sugarcane production in various environments.